Helio Gallardo, an indispensable heretic - Rauber, Isabel (2023)
In this intervention, the heretical component of Helio Gallardo is emphasized through four aspects: i) that which proposes toquestion concepts such as "class" and "subject" to recognize, first, social actors and political actors; ii) the transitional process through which the social actor becomes a political actor; iii) the relationship between politics and those who act in it, a relationship that always concerns the process of recognition and self-recognition of popular subjects in the face of the dominant power; iv) the distinction between political consciousness and ideology, placing special emphasis on the former, since it is in it that the encounter between political situations and the political actions of the actors occurs. Which also highlights the importance of the conjuncture analysis for Helio Gallardo.